THE RATIFICATION OF GENEVA ACT 2015 AS GEOGRAPHICAL INDICATION PROTECTION: THE IMPACT FOR INDONESIA - Disemadi, Hari Sutra (UNISSULA, 2024)
Geographical indications are one of the most important forms of intellectual wealth in the era of free trade, which is an important economic in various countries today. The goods produced by business actors in a country will always affect the representation of the brand and the country of origin. For a country with a diverse cultural and natural resources like Indonesia, geographical indications are one of the important factors in the effort to protect Indonesia’s identity and uniqueness. The increasing urgency of the entry of Indonesian products into the international market has prompted the Indonesian government to seek legal remedies to protect local products that can help strengthen the country’s economy. This research analyzes Indonesia’s interest in ratifying the Geneva Act 2015 through doctrinal legal research method combined with statutory approach. Normative analysis of this study finds that ratifying the Geneva Act 2015 is indeed a step in the right direction, considering the many found weaknesses and normative restriction within the legal framework of geographical indication protection in Indonesia.